Study of Non-Homogeneity of Magnetic Field Distribution in Single-Crystal Ni-Mn-Ga Magnetic Shape Memory Element in Actuators Due to Its Anisotropic Twinned Microstructure - Gabdullin, N.; Khan, S. H. (IEEE transactions on magnetics, 2017)
Magnetic shape memory (MSM) alloys are relatively new and very promising "smart" materials that respond to magnetic fields and exhibit the shape memory effect at room temperature. Maximum strain varies from 6% to 12% of the MSM element's length depending on its microstructure. The shape memory effect and the magnetic field-induced reorientation of MSM twin variants in low-temperature martensite phase have been subject to ongoing research for almost two decades. However, the magnetic field distribution in the MSM elements and effects of its varying magnetic permeability on bias magnetic field are not well studied. In this paper, we present an extension to the existing modeling approach for MSM elements applicable to actuator design. The effects arising from single-crystal anisotropy and demagnetization effects due to non-homogeneous multi-variant MSM microstructure are studied and discussed. The proposed approach is validated by comparing computational results with the previously reported measurement data.